Pengembangan Pregnancy Pillow Therapy Berbasis Serat Daun Nanas dengan Aromaterapi untuk Meningkatkan Kenyamanan Ibu Hamil - Dona Martilova; Muthia Fahira (Lembaga Pengembangan Kinerja Dosen, 2026)
The physiological changes that occur during pregnancy, both physically and mentally, may be rather uncomfortable, particularly in the second and third trimesters. Pregnant women often report back discomfort, muscular aches, trouble sleeping, excessive exhaustion, and irregular sleep patterns. Mothers' physical and mental health as well as the health of their unborn children may be significantly impacted by inadequate sleep quality during pregnancy. To enhance comfort and the quality of sleep during pregnancy, one non-pharmacological technique is to use an aromatherapy maternity pillow. An ergonomic and ecologically sustainable invention to enhance mother comfort during pregnancy was the goal of this research, which intended to produce a Pregnancy Pillow Therapy product with pineapple leaf fiber and aromatherapy. A descriptive research design using a prototype creation technique was used in this study. The stages of the research included problem identification, literature review, product design, material selection, prototype manufacturing, and product evaluation. Data were collected through literature studies and observations related to sleep discomfort in pregnancy, maternity pillow utilization, aromatherapy therapy, and pineapple leaf fiber characteristics. The developed product was designed ergonomically to support the back, abdomen, waist, and legs of pregnant women. The addition of aromatherapy was intended to provide a relaxing effect and improve sleep quality. The use of pineapple leaf fiber also supports environmentally friendly product innovation through agricultural waste utilization. The results indicate that Pregnancy Pillow Therapy has the potential to become a supportive product for improving comfort and sleep quality among pregnant women. Further studies are recommended to evaluate product effectiveness directly among pregnant women.